Resolving Complicated Faulting Process Using Multi‐Point‐Source Representation: Iterative Inversion Algorithm Improvement and Application to Recent Complex Earthquakes. Issue 2 (27th January 2020) - Yue, Han; Lay, Thorne
Abstract: Complicated faulting processes of large earthquakes may involve simultaneous or sequential rupture of multiple fault planes, often with different focal mechanisms. Determination of these subevent focal mechanisms is essential for multifault parameterization and complex rupture process analysis. Iterative inversion for Multi‐Point‐Source (MPS) faulting representations using broadband teleseismic body waves is an established strategy to estimate the focal mechanism variation but tends to be an unstable procedure. We enhance an iterative inversion algorithm developed by M. Kikuchi and H. Kanamori by specifying extra a priori constraints in the inversion. These constraints include the specific search time window, location, and source time function of each point source subevent to enable controls over the temporal and spatial properties of each point source. We apply the improved algorithm to seven recent earthquakes with complex faulting: the 2008 Wenchuan, 2009 Samoa, 2010 El‐Mayor Cucapah, 2010 Darfield, 2012 Indian Ocean, 2016 Kaikoura, and 2018 Gulf of Alaska earthquakes. The faulting complexity of these events has been independently constrained using geodetic, seismic, tsunami, and/or field observations, enabling tests of the MPS inversion algorithm performance. The improved iterative inversion resolves varying focal mechanisms of multiple point sources with specific timing consistent with detailed solutions, but spatial resolution tends to be relatively low (>20 km). Summation of subevent point‐source solutions recovers 30% to 95% of the long‐period point‐source seismic moments, varying with different levels of parameterization. The improved iterative MPS inversion algorithm is a promising approach for prompt (within a few hours) analysis of primary focal mechanism variation with reasonable overall space‐time distribution for complicated events. Key Points: Stripping algorithm‐based Multi‐point‐source inversion algorithm improved from the original version and tested Focal mechanism changes could be resolved by this algorithm Spatial resolution are relatively low using only teleseismic body‐waves